2017
DOI: 10.26444/jpccr/74465
|View full text |Cite
|
Sign up to set email alerts
|

Marginal bone loss around dental implants with various types of implant-abutment connection in the same patient

Abstract: Szymańska J, Szpak P. Marginal bone loss around dental implants with various types of implant-abutment connection in the same patient. J Pre-Clin Clin Res. 2017; 11(1): 30-34. doi: 10.26444/jpccr/74465 Abstract Introduction. One of the criteria of implant therapy success is marginal bone loss. The objective of the study was to assess the correlation between peri-implant marginal bone loss and implant-abutment connection systems used in the same patient, as well as other specific characteristics of implant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…No studies have been found in the literature where this specific software is used. However, there are numerous studies where very similar software is used, specific to radiographic vision, for the assessment of peri-implant marginal bone loss, as is the case of Szymańska et al (12), and Dave et al (13), who use the Planmeca Romexis® software to evaluate the bone loss of the implants according to the neck of these, in the case of the first author, and to compare the diagnosis of peri-implant marginal bone loss with CBCT and with digital periapicals in the case of the second author. In the same sense, there are other authors who also evaluated this bone loss with other softwares of the same group, such as Cassetta et al (7,14), with the VixWinPRO® program, Peñarrocha et al (15), with Digora Optime®, or Van Weehaeghe et al (16), with the Mediadent® program.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have been found in the literature where this specific software is used. However, there are numerous studies where very similar software is used, specific to radiographic vision, for the assessment of peri-implant marginal bone loss, as is the case of Szymańska et al (12), and Dave et al (13), who use the Planmeca Romexis® software to evaluate the bone loss of the implants according to the neck of these, in the case of the first author, and to compare the diagnosis of peri-implant marginal bone loss with CBCT and with digital periapicals in the case of the second author. In the same sense, there are other authors who also evaluated this bone loss with other softwares of the same group, such as Cassetta et al (7,14), with the VixWinPRO® program, Peñarrocha et al (15), with Digora Optime®, or Van Weehaeghe et al (16), with the Mediadent® program.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the studied implant systems, implant treatment, surgical techniques, prosthetic restorations, techniques of peri-implant bone loss measurement and limitations of the research model has been included in the authors' earlier publication [3].…”
Section: Methodsmentioning
confidence: 99%
“…The changes in marginal bone related to time and implant type were described in an earlier paper [3].…”
Section: The Characteristic Of Implant-prosthetic Treatmentmentioning
confidence: 98%